(untitled) (Research, Society and Development, 2022)
Self-injury is defined, in general terms, as self-inflicted damage to the skin without accepted social and cultural ends. The low amount of etiological research on this clinical phenomenon and the more robust data on its epidemiology in Brazil justify the relevance of the research developed together with the Graduate Program in Psychology at the Federal University of Rio de Janeiro. This article presents the findings referring to the first part of the research Cuts in the Skin: Analyzing Self-Injury in the Light of the Clinical Diagnosis Indexes of Anguish Neurosis, dedicated to a systematic review of the literature on the subject of self-injury in order to determine the epidemiological characteristics of the disease. phenomenon and delimit the direction of scientific production on the psychic etiology of self-injury, in the period 2009 and 2018. The survey was organized in two axes: 1. Global and national data on the phenomenon of self-injury in WHO and Ministry of Health documents; 2. Scientific literature produced between 2009 and 2018, in the VHL, Scielo and CAPES Theses Databases. Both surveys were based on scientific production on self-harm, over a period of ten years (2009-2018) and descriptors: 1) Cutting; 2) Cut; 3) Mutilation; 4) Self-mutilation; 5) Self-injury. The results of this review indicate three directions for research in psychoanalytic psychopathology: 1. Self-injury as a way of producing the bond between the subject and the Other; 2. The etiology of self-injury/self-mutilation located in masochism; 3. The etiology of self-injury/self-mutilation located in self-destructiveness.